Genetically-modified vegetables for farmers’ welfare - Singh, Major; Kumar, Rajesh; Prasanna, H. C.; Tiwari, S. K.; Gujjar, R. S.; Karkute, S. G. (Indian Horticulture, 2019)
Transgenic plants are plants that have been genetically engineered using recombinant DNA techniques to create plants with new desired traits. This is generally achieved by inserting gene or genes that express useful traits. Transgenic crops were considered as game changers in agriculture and have been successfully cultivated in various countries. The USA has open-heartedly adopted the technology and ranked top with transgenic crops grown on 73.1 million hectare area in 2014 (http://www.isaaa.org/). India, with Bt cotton as its only biotech crop grown on area of 11.6 million hectare ranked fourth. Brinjal is the first food crop and first vegetable crop which has been approved by GEAC for commercial cultivation.